Risk Perception and Key Beliefs on Business Adaptation Behavior of Family Farmers: Empirical Evidence from Sichuan Province, China - Yu Mou; Xiaofeng Li (Behavioral Sciences)
Family farmers face various business risks, including natural disasters, policies, technology adoption, and market uncertainties. This paper develops a conceptual framework for the formation mechanism of family farmers’ business adaptation behaviors by linking “risk perception, key beliefs, and adaptation behavior”. Using microdata from 363 family farmers in Sichuan Province, China, and applying ordered logit model regression analysis, we find that both risk perception and key beliefs positively influence family farmers’ business adaptation behavior. Key beliefs partially mediate this relationship, while risk preference negatively moderates the effect of risk perception on business adaptation behavior. Additionally, family farmers with higher farm profit levels and larger social networks are more likely to engage in business adaptation behavior. Family farmers who have higher education, are older, operate larger-scale farms, and are male exhibit stronger risk perceptions.